1993
DOI: 10.1073/pnas.90.6.2404
|View full text |Cite
|
Sign up to set email alerts
|

A single bifunctional enzyme, PilD, catalyzes cleavage and N-methylation of proteins belonging to the type IV pilin family.

Abstract: Precursors of the type IV pilins of a number of bacterial pathogens, as weil as related proteins involved in extraceliular protein export and DNA uptake, are synthesized with short basic leader sequences. Maturation of these proteins involves two consecutive posttranslational modifications. The leader sequence is fhrst proteolytically removed by specialized endopeptidases, of which the prototype is encoded by the piD gene of Pseudomonas aeruginosa. Subsequently, the amino termini of these proteins are methylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
198
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(200 citation statements)
references
References 34 publications
1
198
0
1
Order By: Relevance
“…It was noticed later, however, that the IbpA/B-immunogen preparation was contaminated by 16 kDa membrane protein. We found that separation of this protein from IbpA/B by one-dimensional electrophoresis could be achieved using a Tricine-containing buffer (Strom et al, 1993). The newly prepared serum does not recognize the 16 kDa membrane protein and does not react with components of the OM fraction.…”
Section: Estimation Of Fda Activity In Wt(pken8) and Grpe(pken8) Cellmentioning
confidence: 89%
“…It was noticed later, however, that the IbpA/B-immunogen preparation was contaminated by 16 kDa membrane protein. We found that separation of this protein from IbpA/B by one-dimensional electrophoresis could be achieved using a Tricine-containing buffer (Strom et al, 1993). The newly prepared serum does not recognize the 16 kDa membrane protein and does not react with components of the OM fraction.…”
Section: Estimation Of Fda Activity In Wt(pken8) and Grpe(pken8) Cellmentioning
confidence: 89%
“…In addition to the comG proteins, a fourth gene family, exemplified by comC (Mohan et al, 1989), pilD (Strom et al, 1993) and pulO (Dupuy et al, 1992), encodes the peptidases required for processing of pre-pilin-like proteins. Indeed, we have shown that ComGC is processed by a pathway that requires the product of comC (Chung and Dubnau, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Low-copy-number cloning vector Wang & Kushner (1991) quence and N-methylates the new amino terminus of the pilin (Strom et al, 1993). Pre-pilin peptidases compose a unique class of bi-lobed aspartate proteases (LaPointe & Taylor, 2000).…”
Section: Introductionmentioning
confidence: 99%